On large deviations for compound mixed Poisson process - Kasparavičiūtė, Aurelija; Deltuvienė, Dovilė (Lietuvos matematikos rinkinys, 2013)
This paper is designated for normal approximation to the distribution function of the compound mixed Poisson process taking into consideration large deviations both in the Cramér and power Linnik zones.